2009
DOI: 10.1007/s10592-009-9959-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and uncertain taxonomic status of threatened Foskett Spring speckled dace

Abstract: Foskett Spring is a small isolated desert spring in the Warner Basin of Oregon containing an undescribed subspecies of speckled dace protected under the US Endangered Species Act. Uncertainty regarding the taxonomic status of Foskett dace has raised questions about their evolutionary relationship to other more abundant populations in the Warner Basin. To address these questions, we sequenced 1,982 base pairs (bp) of the ND2 and cyt-b genes of mitochondrial DNA (mtDNA) for 85 fish from Foskett Spring, the surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…In their study of mtDNA variation in Richardsonius , Houston et al [ 56 ] found most variation distributed among, but not within, major regions, indicating high levels of gene exchange within but not among regions. This contrasts with studies of other minnows (e.g., Rhinichthys osculus –[ 57 , 58 ] and Lepidomeda –[ 59 ]), where there was considerable divergence among localities within drainages as well as among drainages. Johnson [ 60 ] also identified considerable divergence within and among drainage groups in the cyprinid Gila atraria but also noted additional divergence associated with evolved life history differences within this species.…”
Section: Discussioncontrasting
confidence: 66%
“…In their study of mtDNA variation in Richardsonius , Houston et al [ 56 ] found most variation distributed among, but not within, major regions, indicating high levels of gene exchange within but not among regions. This contrasts with studies of other minnows (e.g., Rhinichthys osculus –[ 57 , 58 ] and Lepidomeda –[ 59 ]), where there was considerable divergence among localities within drainages as well as among drainages. Johnson [ 60 ] also identified considerable divergence within and among drainage groups in the cyprinid Gila atraria but also noted additional divergence associated with evolved life history differences within this species.…”
Section: Discussioncontrasting
confidence: 66%
“…These levels of genetic diversity may not be unusual in spring biota, as they exist in very isolated and small habitat patches and undergo strong selection pressure to adapt to local conditions. Further examples include a study of speckled dace from Foskett Springs, USA that also detected three cytb haplotypes (Arden et al , ), and haplotype diversity per spring group was also found to be relatively low in the Trochidrobia spring snails (Murphy et al , ), and the Bitter Lake National Wildlife Refuge endemic spring snails (Morningstar et al , ). Even though low levels of cytb diversity may be the natural evolutionary state for spring biota, further population genetic monitoring of Edgbaston goby is advised as recent surveys have suggested it is also in decline across the spring system (Kerezsy, ).…”
Section: Discussionmentioning
confidence: 99%
“…More narrowly, Ardren et al (2010) applied mtDNA analysis to dace from throughout the Warner Basin and concluded that the lineages could collectively qualify as a species. Hoekzema and Sidlauskas (2014) also examined SDC fish from the Warner Basin along with dace from five other isolated Great Basin populations in Oregon.…”
Section: Introductionmentioning
confidence: 99%